A critical time window for recovery extends beyond one-year post-stroke - Ballester, Belén Rubio; Maier, Martina; Duff, Armin; Cameirão, Mónica; Bermúdez, Sergi; Duarte, Esther; Cuxart, Ampar; Rodríguez, Susana; San Segundo Mozo, Rosa María; Verschure, Paul F. M. J. (Journal of neurophysiology, 2019)
The impact of rehabilitation on post-stroke motor recovery and its dependency on the patient’s chronicity remain unclear. The field has widely accepted the notion of a proportional recovery rule with a “critical window for recovery” within the first 3–6 mo poststroke. This hypothesis justifies the general cessation of physical therapy at chronic stages. However, the limits of this critical window have, so far, been poorly defined. In this analysis, we address this question, and we further explore the temporal structure of motor recovery using individual patient data from a homogeneous sample of 219 individuals with mild to moderate upper-limb hemiparesis. We observed that improvement in body function and structure was possible even at late chronic stages. A bootstrapping analysis revealed a gradient of enhanced sensitivity to treatment that extended beyond 12 mo poststroke. Clinical guidelines for rehabilitation should be revised in the context of this temporal structure. NEW & NOTEWORTHY Previous studies in humans suggest that there is a 3- to 6-mo “critical window” of heightened neuroplasticity poststroke. We analyze the temporal structure of recovery in patients with hemiparesis and uncover a precise gradient of enhanced sensitivity to treatment that expands far beyond the limits of the so-called critical window. These findings highlight the need for providing therapy to patients at the chronic and late chronic stages.